2018
DOI: 10.1159/000491088
|View full text |Cite
|
Sign up to set email alerts
|

A Rationale for Timing of Luteal Support Post Gonadotropin-Releasing Hormone Agonist Trigger

Abstract: Gonadotropin-releasing hormone (GnRH) antagonist-based ovarian stimulation protocol is gaining popularity. This protocol allows for the use of GnRH agonist as a trigger of final oocyte maturation, instead of the “gold standard” human chorionic gonadotropin (hCG) trigger. GnRH agonist trigger causes quick luteolysis, hence its widespread use in the context of ovarian hyperstimulation syndrome (OHSS) prevention. To secure pregnancy post GnRH agonist trigger, the luteal phase must be supplemented to counteract th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Despite data on its efficacy and safety, it has been recognized that GnRH-a triggering may not result in an adequate oocyte yield and has an adverse impact on pregnancy outcomes in patients with low LH on the triggering day [18,[53][54][55] . GnRH-as trigger the release of endogenous LH from the pituitary gland and cause rapid luteolysis, leading to luteal phase deficiency [56,57] . Therefore, patients with low LH levels may not be suitable candidates for treatment with GnRH-as.…”
Section: Discussionmentioning
confidence: 99%
“…Despite data on its efficacy and safety, it has been recognized that GnRH-a triggering may not result in an adequate oocyte yield and has an adverse impact on pregnancy outcomes in patients with low LH on the triggering day [18,[53][54][55] . GnRH-as trigger the release of endogenous LH from the pituitary gland and cause rapid luteolysis, leading to luteal phase deficiency [56,57] . Therefore, patients with low LH levels may not be suitable candidates for treatment with GnRH-as.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies (4,5) at home and abroad have shown that the application of the gonadotropin-releasing hormone agonist (GNRH-a) during chemotherapy has a protective effect on the ovarian function of cervical cancer patients who undergo the TP chemotherapy regimen (6). Cervical cancer is a common clinical gynecological disease.…”
Section: Original Articlementioning
confidence: 99%
“…Recently, several publications examined cycles that were triggered with a GnRH agonist to reduce the risk for OHSS, but that subsequently proceeded with a fresh ET. The challenges in designing LPS post GnRH agonist are the higher chances for rapid luteolysis on one hand, and the need to reduce the risk for OHSS on the other ( 15 ). Elgindy et al ( 16 ) conducted a RCT comparing IM vs. vaginal progesterone administration in patients with increased baseline OHSS risk that were triggered with either GnRH agonist or 5,000 IU of HCG.…”
Section: Introductionmentioning
confidence: 99%